The Status Of Deeds Of Shareholders’ General Meeting Made By Notary Through Teleconference Media Based On The Law Number Two Of 2014 - Saptarina, Vina (Magister Kenotariatan Universitas Pasundan, 2023)
The provisions of Law Number 40 of 2007 concerning limited liability companies, specifically Article 77 Paragraph (1), stipulate that a General Meeting of Shareholders (hereinafter referred to as GMS) can be conducted through teleconferencing. Naturally, this provision facilitates shareholders in convening GMS meetings. Yet, in this case, Law Number 40 of 2007 does not provide a comprehensive explanation of the procedures for organizing a General Meeting of Shareholders (GMS). The organization of a General Meeting of Shareholders (GMS), wherein the minutes of the meeting are crafted directly by a notary in the form of an authentic deed, must conform to the regulations as stipulated in Law Number 40 of 2014 regarding the role and position of a notary. It is important to note that the minutes of a GMS conducted via teleconference, the aforementioned documentation, which will later be formalized into an authentic deed by a notary, must still adhere to the stipulations set forth in notary law. This compliance is essential due to the legal implications associated with the authentic deed and its impact on the notary's professional responsibilities. In this study, the normative-legal method was employed to analyze legal issues arising from and related to legal norms, as stipulated in statutory regulations. This approach was complemented by a library research method, specifically involving the examination of library materials. During this phase, the analysis of secondary data was conducted, encompassing an exploration of the legal norms, laws, and regulations applicable in Indonesia.